A static organization in a dynamic context – A qualitative study of changes in working conditions for Swedish engine officers. (July 2016) - Lundh, Monica; Rydstedt, Leif W.
Abstract: During the last decades the shipping industry has undergone rapid technical developments and experienced hard economic conditions and increased striving for profitability. This has led to reduced staffing and changes in task performance, which has been reported to increase workload for the remaining seafarers. The working conditions on board have a number of distinct and in many ways unique characteristics, which makes the job demands and resources for seafarers unique in several ways. The purpose of this study was to assess how engine room staff perceives how these major technical and organizational changes in the shipping industry have affected job demands as well as resources. The study compiled individual interviews and focus groups interviews with engine crew members where they were asked to elaborate on the psychosocial work environment and the major changes in the working conditions on board. Engine crew describes a work situation where they feel a lack of resources. The content of the work has changed, staffing has been reduced, new tasks are being added but the organization of the crew and the design of the work place remains unaltered. Highlights: Maritime engine room officers commonly agree that the rapid technological development and reduced staffing onboard have contributed to higher workload and altered work tasks. Engine room officers have not been given enough or proper resources to handle the new requirements of the altered working conditions in the shipping industry. Collegial support and comradeship are seen as the main resources of the onboard organization.